Management of Instability following Pyogenic Sacroiliitis: Technical Case Report - Passaplan, C. (Case Rep Orthop, 2020)
BACKGROUND: Septic arthritis of the sacroiliac joint (SI-joint) is a rare and often delayed diagnosis. Management usually consists of intravenous antibiotics and debridement of infected tissue. However, very few reports consider the management of the secondary instability of the sacroiliac joint. Case Presentation. We report a case of a 16-year-old girl diagnosed with S. aureus pyogenic sacroiliitis who benefited from aggressive surgical debridement and primary arthrodesis for infection-related SI-joint instability in the acute infection phase. CONCLUSION: Diagnosis of pyogenic sacroiliitis is often delayed. Destruction of the joint can lead to chronic pain and instability. In cases of obvious intraoperative instability, primary arthrodesis could be considered in young patients.